Investigating the internal structure and mechanical properties of graphene nanoflakes enhanced aluminum foam. (15th November 2017) - An, Yukun; Yang, Siyi; Wu, Hongyan; Zhao, Ertuan; Wang, Zongshen
Abstract: The manuscript focuses on analyzing the pore morphology and pore distribution of novel graphene nanoflakes reinforced aluminum foam (GNF-AF) and investigating their mechanical properties under quasi-static compressive loadings. Experimental results indicate the existence of GNFs can reduce the pore diameter, refine the pore morphology, and improve the pore distribution. Distinguish from other brittle foams, GNF-AF presents smooth stress-strain curve, wherein the local buckling deformation, shear deformation, tensile deformation combinate the whole compressive behavior. By comparing the plateau stress, energy absorption, and specific energy absorption of GNF-AF with varying content of GNFs, a notable improvement of 29.0%, 28.5%, and 27.9% was detected by adding 0.10 wt% GNFs. Besides, the energy absorption efficiency of enhanced aluminum foam was slightly improved. Graphical abstract: Highlights: Adding 0.1 wt% graphene nanoflakes can improve the pore morphology and the pore distribution. Local buckling deformation, shear deformation, and tensile deformation constituted the compressive behavior of GNF-AF. The strengthening mechanical for GNF-AF was constituted by matrix strengthening and internal structure strengthening. Plateau stress, energy absorption, and specific energy absorption were enhanced by adding 0.1 wt% GNFs.